THU0031 Factors Associated with Fatigue in Systemic Lupus Erythematosus Patients. (10th June 2014) - Lisitsyna, T.A.; Veltishchev, D.; Gerasimov, A.; Seravina, O.; Kovalevskaya, O.; Marchenko, A.; Krasnov, V.; Nasonov, E.
Abstract : Background: evidence exists that fatigue is a significant problem for systemic lupus erythematosus (SLE) patients (pts). The causes of fatigue aren't enough investigated. SLE activity and depression are confounding fatigue factors. Objectives: to determine the prevalence of fatigue in SLE pts and it's associations with some disease features. Methods: 150 SLE-pts were enrolled in this study. All of them met the full ACR revised criteria for SLE classification. 85, 6% SLE pts were women with a mean age of 34, 6±0, 93 yrs (M±m). The disease activity was assessed by SLEDAI. Mean SLEDAI score was 9, 13±0, 63 point (M±m). The damage due to SLE was measured by SLICC/ACR DI. 91, 1% SLE pts were taking prednisone in mean daily dose 19, 3±1, 11 mg (M±m). 40, 6% SLE pts were taking cyclophosphamide, azathioprine or mycophenolate mofetil. Psychiatric disorders were diagnosed by psychiatrist in accordance with the DSM-IV. Psychiatric scales used: Hospital Anxiety and Depression Scale; short and long memory tests, mediated memorizing test; attention tests, projective test "pictogram", sentence completion test, "exclusion of objects" test for evaluation of cognitive functions. Major depressive disorder was detected in 21, 3% and minor depressive disorder - in 32, 7% of SLE pts. Mild cognitive impairment (MCI) was diagnosed in 36, 1% of SLE pts. Fatigue was evaluated using Fatigue Severity Scale (FSS). Quality of life (QoL) was evaluated using EQ-5D scale. Results: 88 (58, 7%) SLE pts had clinically relevant fatigue (≥4). The presence of fatigue didn't depend on age, gender, duration of disease, SLEDAI and SLICC/ACR DI score, hemoglobin and ESR levels. The significant differences were found in number of SLE pts with major (RR=3, 80) and minor (RR=4, 22) depressive disorders, sleep disturbances (RR=2, 41) and MCI (RR=2, 94) in pts with vs without fatigue (p<0, 001). SLE pts with fatigue were taking more prednisone daily (20, 0 (10, 0; 30, 0) vs 10, 0 (7, 5; 30, 0) mg, p=0, 046), had the most maximum (50, 0 (30, 0; 60, 0) vs 40, 0 (20, 0; 50, 0) mg, p=0, 005) and cumulative dose of prednisone (35, 2 (9, 27; 64, 3) vs 18, 2 (4, 34; 47, 7) gram, p=0, 030) and cyclophosphamide (3, 2 (0; 10, 7) vs 0, 4 (0; 4, 8) gram, p=0, 015) (data presented as median and IQR). The QoL (EQ-5D) was lower in SLE pts with fatigue (0, 63±0, 03 vs 0, 88±0, 02, p<0, 001) (M±m). In a linear regression model the presence of depressive disorders (β=0, 269), sleep disturbances (β=0, 168), MCI (β=0, 168), maximum dose of prednisone (β=0, 172) and cumulative dose of cyclophosphamide (β=0, 103) were independently associated with clinically relevant fatigue in SLE pts (area under the ROC curve=0, 934). Conclusions: the results demonstrated high prevalence of fatigue in surveyed SLE pts. Fatigue in SLE is a complex condition which is much more associated with the diagnosis of depressive disorder, accompanied by sleep disturbances and MCI, with maximum dose of prednisone and cumulative dose of cyclophosphamide and has a negative impact on QoL. The current disease activity of SLE didn't exert influence on fatigue. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.2158